(3eHGOF JShjb TQcGJ GdWjQGfs - (3GdMhGQj(B, (3fVGd YHGSs; (3GHQGgje NGdOs ((3YeGfs (3OGQ UaGA ddfTQ hGdJhRjYs, 2002)
(3ebOeI aj GdJShjb(B- (3HMhK GdJShjb(B- (3GdHjFI GdJShjbjI(B- (3JbSje GdShb(B- (3SdYI GdWjQGf(B- (3JcGdja Yed GdWGFQI(B- (3GdJSYjQ(B- (3eaghe GdJQhjL(B- (3bfhGJ GdJhRjY(B.s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdNWhW GdLhjIs